Seeds, fruits and nuts in the Scottish Mesolithic - Bishop, Rosie R; Church, Mike J; Rowley-Conwy, Peter A (Proceedings of the Society of Antiquaries of Scotland, 2014)
Over the past few decades, the potential importance of plants within European Mesolithic economies has frequently been discussed, but there has been little systematic consideration of the archaeobotanical evidence for Mesolithic plant consumption in Scotland. This paper assesses the use of plants in the Scottish Mesolithic economy using the archaeobotanical evidence from 48 sites. It is argued that plants were systematically, and, in some cases, intensively, exploited in Mesolithic Scotland. Though plan remains were extremely sparse at most sites, it is suggested that uneven archaeological sampling and taphonomic factors, together with the relatively short duration of occupation of many sites, may be responsible for the restricted range and frequency of edible tax in most assemblages.